FACEHBI: A PROSPECTIVE STUDY OF RISK FACTORS, BIOMARKERS AND COGNITION IN A COHORT OF INDIVIDUALS WITH SUBJECTIVE COGNITIVE DECLINE. STUDY RATIONALE AND RESEARCH PROTOCOLS - Rodriguez-Gomez, O.; Sanabria, A.; Perez-Cordon, A.; Sanchez-Ruiz, D.; Abdelnour, C.; Valero, S.; Hernandez, I.; Rosende-Roca, M.; Mauleon, A.; Vargas, L.; Alegret, M.; Espinosa, A.; et al. (The Journal of Prevention of Alzheimer's Disease, 2017)
Background: Long-term longitudinal studies with multimodal biomarkers are needed to delve into the knowledge of preclinical AD. Subjective cognitive decline has been proposed as a risk factor for the development of cognitive impairment. Thus, including individuals with SCD in observational studies may be a cost-effective strategy to increase the prevalence of preclinical AD in the sample. Objectives: To describe the rationale, research protocols and baseline characteristics of participants in the Fundació ACE Healthy Brain Initiative (FACEHBI). Design: FACEHBI is a clinical trial (EudraCT: 2014-000798-38) embedded within a long-term observational study of individuals with SCD. Setting: Participants have been recruited at the memory clinic of Fundació ACE (Barcelona) from two different sources: patients referred by a general practitioner and individuals from an Open House Initiative. Participants: 200 individuals diagnosed with SCD with a strictly normal performance in a comprehensive neuropsychological battery. Measurements: Individuals will undergo an extensive neuropsychological protocol, risk factor assessment and a set of multimodal biomarkers including florbetaben PET, structural and functional MRI, diffusion tensor imaging, determination of amyloid species in plasma and neurophthalmologic assessment with optical coherence tomography. Results: Two hundred individuals have been recruited in 15 months. Mean age was 65.9 years; mean MMSE was 29.2 with a mean of 14.8 years of education. Conclusions: FACEHBI is a long-term study of cognition, biomarkers and lifestyle that has been designed upon an innovative symptom-based approach using SCD as target population. It will shed light on the pathophysiology of preclinical AD and the role of SCD as a risk marker for the development of cognitive impairment.